Simulator Proses Pengisian dan Pemasangan Tutup Botol Terkendali PLC Berbantuan Miniatur Konveyor - Anang Dwi Purnomo; Arief Goeritno; Danang Adi Nugroho (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
A miniature conveyor machine assisted by embedded systems and controlled by a programmable logic controller (PLC) has been fabricated with the operating mechanism is based on the detection of two different colors. The objectives of this research are to obtain a miniature machine is controlled by the PLC system, create a ladder diagram-based program structure, and measure the performance of the embedded system. Obtaining the machine is carried out through assembly of the conveyor frame, installation of all devices, and integrated wiring. The programming for the Omron PLC system is based on providing the CX-Programmer 64 bits, establishing algorithms and compiling ladder diagrams, and compiling and uploading processes. The performance measurement includes synchronization conditions between the simulator and the control system, observations of the readings of installed sensors for activating all devices on the output side, and observing the measurement of the filling process time and the installation of bottle caps assisted by the pneumatic system. The results of the performance during the process of filling and installing the lid obtained a success rate of 75%, based on four trials, three successes, and one failure. The general conclusion is that the embedded system that has been built can be used as a simulator for the mechanism of filling liquid into bottles and installing bottle caps, and it is as an implementation of instrumentation and automation processes.